The influence of cabergoline on the offspring phenotype of human chorionic gonadotropin (hCG)- secreting female mice: does mother's milk make the difference? - Marcial López, Carla Agustina (2021)
Transgenic female mice expressing human chorionic gonadotropin-ß (hCGß +) produce elevated levels of hCG, prolactin and progesterone, show precocious puberty, are infertile and develop pituitary tumors. We have previously demonstrated that a short-term treatment of juvenile hCGß + females with the dopamine agonist cabergoline normalizes the phenotypic changes of hCGß + females. Even more, the treatment prevented phenotypic alterations on the transgenic offspring. The aim of this study was to determine if the cabergoline treatment has its effect during pregnancy and/or lactation. Two groups of 2-month-old wild-type (WT) females were mated with hCGß + males: (1) Six-week-old WT females pretreated with cabergoline (500 µ g/kg, ip), every other day for one week (WT-CAB mothers); (2) WT females without treatment (WT- mothers).